CONTENT ANALYSIS OF SOCIAL EXPECTATIONS OF FUTURE SOCIAL PSYCHOLOGISTS - Popovych, Igor; Blynova, Olena (PSYCHOLOGICAL JOURNAL, 2019)
The article analyzes social expectations of future social psychologists, examines the results of research on the peculiarities of social expectations, and establishes psycholinguistic determinants of constructing social reality by personality. It is emphasized that the variability of the demands of social environment predetermines the need for constant prognostic activity of the subject of life activity, not only in relation to natural object relations, but also in the sphere of social interaction, social communication, and speech constructing practices in the form of peculiar social expectations. It is substantiated and proven that the strict quantification of texts, creation of a coding matrix, quantitative and qualitative content analysis, the empirical distribution of scales at all levels of the investigated parameters, the determination of correlation, ensure reliability, reliability and validity of the research of the psycholinguistic aspect of the social expectations of future social psychologists. It is established that the future social psychologists by the properties of social expectations showed such indices: internality (51.43%), not contradicting the results obtained by other researchers; activity (57.13%), the results of which almost coincide with the internality by the quantitative and percentage values; moderate results of openness (47.52%), which may indicate maturity and social competence of one part of the subjects and at the same time inability or unwillingness to interpret, outline their expectations – the second part of the subjects. It is proved that future social psychologists, interpreting the social field – define it, pay great attention to reflective aspects, take the position of «participant in the process». It is noted that taking into account the age-related, interesting features of the sample objectively reflected the measurement of the properties of the expected social reality and indicated the quantitative and qualitative psychological parameters of the social expectations of personality. It is proved that the content analysis allows measuring human behavior. It is shown how the sign-semantic formations acquire subjective meanings, become objective factuality, that influence the construction of the social reality by the personality.